2006
DOI: 10.1086/498992
|View full text |Cite
|
Sign up to set email alerts
|

Strong Genetic Evidence of DCDC2 as a Susceptibility Gene for Dyslexia

Abstract: We searched for linkage disequilibrium (LD) in 137 triads with dyslexia, using markers that span the most-replicated dyslexia susceptibility region on 6p21-p22, and found association between the disease and markers within the VMP/DCDC2/KAAG1 locus. Detailed refinement of the LD region, involving sequencing and genotyping of additional markers, showed significant association within DCDC2 in single-marker and haplotype analyses. The association appeared to be strongest in severely affected patients. In a second … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

5
254
4
9

Year Published

2006
2006
2012
2012

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 218 publications
(272 citation statements)
references
References 25 publications
5
254
4
9
Order By: Relevance
“…Multivariate linkage analysis had previously shown that the DYX2 QTL influenced variability shared by all the DD measures but did not influence IQ, 24 and univariate quantitative linkage analysis using IQ-adjusted traits refined the linkage signal. 17 Therefore, all quantitative measures used in the present study were IQ-adjusted as in Francks et al 17 As previous evidence had indicated that the DYX2 locus influences the most severely affected with reading disability, 17,21,25 we used the same subsample of sibships as in Francks et al, 17 that is scoring below a mean measure calculated on phonological decoding ability and orthographic coding, which were the two measures contributing most to the linkage signal. This selection yielded 126 families, including 313 siblings.…”
Section: Subjectsmentioning
confidence: 99%
See 4 more Smart Citations
“…Multivariate linkage analysis had previously shown that the DYX2 QTL influenced variability shared by all the DD measures but did not influence IQ, 24 and univariate quantitative linkage analysis using IQ-adjusted traits refined the linkage signal. 17 Therefore, all quantitative measures used in the present study were IQ-adjusted as in Francks et al 17 As previous evidence had indicated that the DYX2 locus influences the most severely affected with reading disability, 17,21,25 we used the same subsample of sibships as in Francks et al, 17 that is scoring below a mean measure calculated on phonological decoding ability and orthographic coding, which were the two measures contributing most to the linkage signal. This selection yielded 126 families, including 313 siblings.…”
Section: Subjectsmentioning
confidence: 99%
“…To attempt replication of the association observed in DCDC2, we selected those polymorphisms from the German and US studies 20,21 that showed the most significant association either as single markers, or as part of a haplotype. Markers genotyped in both the Oxford and Cardiff samples were the two SNPs (rs807724 and rs1087266) and the intronic deletion identified by Meng et al, 20 and the two SNPs forming the haplotype implicated by Schumacher et al 21 (rs793862 and rs807701).…”
Section: Dcdc2 Analysismentioning
confidence: 99%
See 3 more Smart Citations